Cooling by melting precipitation in Alpine valleys: An idealized numerical modelling study - Unterstrasser, S.; Zängl, G. (Quarterly journal of the Royal Meteorological Society, 2006)
In this study, cooling by melting precipitation in Alpine valleys is investigated. This phenomenon can occur if the initial freezing level is sufficiently far below the crest height of the surrounding mountain ridges so that the air mass in the valley can become decoupled from the environmental flow. In this case, the latent heat required for melting the falling snow is continuously removed from the valley air until the snowline reaches the valley bottom. An analytical heat budget calculation indicates that the reduction of the air volume related to the mountains encompassing a valley significantly reduces the amount of precipitation needed to cool the air in a valley compared to a plain region. However, the impact of this so‐called volume effect on the precipitation amounts is smaller than the geometrical volume factor frequently considered in the context of valley‐wind circulations. Numerical simulations with a highly idealized two‐dimensional model indicate an even smaller volume effect, which might be partly due to numerical inaccuracies. We also examined the impact of an air‐mass exchange between the upper part of the valley atmosphere and the environment. It is found that the warm‐air advection resulting from this air‐mass exchange induces a bifurcation in the temperature evolution of the valley atmosphere. If the temperature advection exceeds a certain threshold value depending on the precipitation intensity and on the height of the initial freezing level, no significant cooling is obtained. For weaker advective warming, the valley atmosphere is cooled and the freezing level eventually reaches the valley bottom if the precipitation lasts long enough. The transition zone between the two regimes is fairly narrow, implying that forecasting real events of cooling by melting is subject to a large uncertainty. Our results also suggest that resolving the turbulent eddies that form below the melting layer is important for realizing the volume effect, which implies that mesoscale numerical models with parametrized turbulence will systematically underestimate the cooling effect in Alpine valleys. Copyright © 2006 Royal Meteorological Society